Public awareness of sickle cell disease in Bahrain - Al Arrayed, Shaikha (Medknow Publications, 2010)
BACKGROUND AND OBJECTIVES: Previous studies that have assessed patient awareness of the management of sickle cell disease (SCD) indicated a lack of awareness of the disease and possibly a need for more public education. Therefore, we measured public awareness in Bahrain of SCD. METHODS: The study was conducted from December 2006 to February 2007. A questionnaire was distributed among 2000 persons selected from among the general public. The participants had face-to-face interviews with either a health professional or a trained interviewer. RESULTS: Most (93%) had heard of SCD and 89% knew that it can be diagnosed by a blood test, but 51% did not know the prevalence of SCD in Bahrain. Eighty-four percent recognized it as a hereditary disorder and 72% said that it can skip generations. Females showed better knowledge than males and married persons seems to know more about SCD than unmarried ones. CONCLUSION: There is a good level of knowledge about SCD among the public, though some of the respondents were confused about the difference between the carrier state of a disease and the disease itself. There is wide acceptance and appreciation of the SCD prevention campaigns being conducted in Bahrain, such as the premarital service and the student screening program.